Recovery time optimization to facilitate motor learning during sprint intervals - Merlau, S. (Strength and Conditioning Journal, 2005)
This manuscript explores the relationship between recovery, fatigue, and specificity of training during the performance of high-intensity, short-duration sprint intervals. Evidence suggests that specificity of training is more critical to the adaptation of sophisticated or advanced motor programs, and that recovery durations of 6 minutes or greater should minimize fatigue, maintain specificity of training, and maximize motor learning when training involves the performance of 60-m sprint intervals.